In vitro Evaluation of Antibacterial Activity of Synthetic Zeolite Supported AgZno Nanoparticle Against a Selected Group of Bacteria - Wakweya B; Jifar WW (Journal of Experimental Pharmacology, 2023)
Berhanu Wakweya,1 Wakuma Wakene Jifar2 1Department of Chemistry, College of Natural and Computational Sciences, Mattu University, Mettu, Oromia, Ethiopia; 2Department of Pharmacy, College of Health Sciences, Mattu University, Mettu, Oromia, EthiopiaCorrespondence: Wakuma Wakene Jifar, Department of Pharmacy, College of Health Sciences, Mattu University, P.O. Box 318, Mettu, Oromia, Ethiopia, Tel +251963421238, Email wakewakish05@gmail.comBackground: The development of novel and intriguing nanoparticle (NP)-based materials with antibacterial activity has recently received attention due to the problem of bacterial resistance to conventional antibiotics becoming more and more frequent. Thus, this study aimed to investigate the antibacterial effectiveness of a synthetic zeolite-supported AgZnO nanoparticle against selected bacteria in vitro.Methods: Using the disc diffusion method, the antibacterial activity of synthetic zeolite-supported AgZnO nanoparticles was assessed against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Zinc oxide (ZnO) and Ag/ZnO nanoparticles were used to create the zeolite-supported Ag/ZnO composite. Chloramphenicol was used as a standard drug. The nanoparticles and composites were characterized using powder X-ray diffraction (XRD), Fourier transform infrared (FTIR), and atomic absorption spectroscopy (AAS).Results: Synthetic zeolite-supported AgZnO nanoparticles showed promising antibacterial properties with the largest zone of inhibition against S. aureus bacteria in comparison to E. coli. The synthetic zeolite-supported AgZnO nanoparticle displayed a zone of inhibition against S. aureus and E. coli without a remarkable difference compared to the respective standard drug (Chloramphenicol). Zinc peaks were visible in the X-ray diffractograms, which supported the theory that the characteristic hexagonal wurtzite structure of zinc oxide was present.Conclusion: All types of ZnO, AgZnO, and AgZnO-Zeolite showed wide-spectrum activity with better effect against gram-positive bacteria, while the Zeolite-Ag/ZnO composite showed even better antibacterial activity. The findings suggest a potential bactericide that needs further evaluation in future studies was observed in synthetic zeolite-supported Ag/ZnO nanoparticles.Keywords: nanoparticles, zeolite, Ag/ZnO nanoparticles, antibacterial activity